Pencitraan Sosial Media - Intan Yulia Saragih; Gde Indra Bhaskara (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
This research is based on widespread use of social media as an image for all people and as well as provides benefits for a company. The large number of social media users makes an American travel site provides reviews about travel related content and this includes reviews of restaurants. Hence, this study discusses the case study of TripaAdvisor's review of the five best restaurants in Bali. With various forms of benefits regarding the benefits of information from TripAdvisor, online reviews from consumers in promoting restaurants and consumer reviews in enhancing the image of a restaurant. The research method used is content analysis method to review from five restaurants, the variables were the value of Food, Service, Value and Atmosphere from these five restaurants and ranked five restaurants through an assessment of consumer reviews on TripAdvisor. The data source is through primary data and secondary data, namely through TripAdvisor. The description of this research is to look at every consumer online review on TripAdvisor, by choosing five of the best TripAdvisor restaurants in Bali and taking 50 consumer reviews from the top five TripAdvisor restaurants in Bali to see the benefits of these consumer reviews in promoting and improving the image of these five restaurants. The results of this study indicate that TripAdvisor is very useful in providing information to restaurants and with consumer reviews can be a tool for restaurant's promotion and able to enhance the image of a restaurant. Keywords : TripAdvisor, Consumer reviews, Restaurants, Bali